TRLS-02. A PILOT STUDY OF EVALUATING EARLY TREATMENT RESPONSE OF BRAIN METASTASES AFTER STEREOTACTIC RADIOSURGERY USING DYNAMIC SUSCEPTIBILITY-WEIGHTED PERFUSION MAGNETIC RESONANCE IMAGING. (12th August 2019) - Huang, Jiayi; Rao, Yuan; Milchenko, Mikhail; LaMontagne, Pamela; Abraham, Christopher; Robinson, Clifford; Wan, Leping; Shimony, Joshua; Rich, Keith; Benzinger, Tammie
Abstract: PURPOSE: To determine if dynamic susceptibility-weighted perfusion magnetic resonance imaging (DSC-PMR) can be used to predict local recurrence (LR) of brain metastases after stereotactic radiosurgery (SRS). METHODS: This is a prospective observational study of adult brain metastasis patients treated with single-fraction SRS, who were imaged with DSC-PMRs before SRS and after 1 week. DSC-PMRs were performed with tracer method in which injection of gadolinium was followed by repeated T2*-weighted gradient echo-planar image acquisition. Regions of interests (ROIs) were generated based on the T1-enhancing tumors irradiated. Relative cerebral blood volume (rCBV) and relative cerebral blood flow (rCBF) parameter maps were calculated by dividing the top 5% of CBV or CBF values within a ROI by the contralateral normal thalamus. LR was determined according to the RECIST 1.1 criteria. Cox regression was conducted to identify factors associated with time to LR. LR rates were estimated with the Kaplan-Meier method and compared using log-rank test. RESULTS: Twenty-three patients were enrolled from 2013 through 2016, with 24 evaluable lesions from 17 patients. After a median follow-up of 12.8 months (range: 3.0–53.7), 5 lesions (21%) developed LR after a median of 3.4 months (range: 2.3–5.7). On univariable analysis, higher rCBV at week 1 (HR 1.06, 95% CI 1.01–1.11, p=0.02), lower SRS dose (HR 0.43, 95% CI 0.20–0.91, p=0.03), and larger tumor volume (HR 1.52, 95% CI 1.05–2.20, p=0.03) were significantly associated with LR, but not histology, rCBV at baseline, change of rCBV at week 1 from baseline, or any rCBF parameters. Higher rCBV at week 1 (above the median) was associated with significantly higher risk of LR than lower rCBV (44% vs 0% at 1 year, respectively, p=0.02). CONCLUSIONS: DSC-PMR and specifically rCBV at week 1 may be a promising imaging biomarker to predict treatment response of brain metastasis after SRS and warrant further investigation.